The Low-Barrier Double-Well Potential of the Oδ1−H−Oδ1 Hydrogen Bond in Unbound HIV Protease: A QM/MM Characterization - Porter, Melissa A; Molina, Pablo A (Journal of chemical theory and computation, 2006)
The presence of a low-barrier hydrogen bond (LBHB) in aspartyl proteases and its implications in drug design have been the subject of intense study. Here, we present a combined quantum mechanical/molecular mechanical (QM/MM)−Numerov procedure and use it to characterize the Oδ1−H−Oδ1 hydrogen bond (HB) in unbound HIV protease. The QM/MM scheme fully traces the shape of the HB's potential energy curve. The potential is used to obtain numerical solutions to the wave functions and vibrational energies of hydrogen, deuterium, and tritium. The vibrational eigenfunctions are used to compute expectation values for interatomic distances and vibrationally and thermally averaged spectroscopic properties of the Oδ1−H−Oδ1 HB. Our work corroborates previous results by Piana and Carloni who found a LBHB via an ab initio molecular dynamics simulation (Piana, S.; Carloni, P. Proteins 2000, 39, 26−36). Our predictions of isotope effects on the chemical shift of unbound HIV protease are consistent with experimental measurements in similar HBs. These results support the predictive power of this method and its potential use in screening inhibitors of aspartyl proteases.